Própolis: produto natural com atividade antibiofilme sobre o gênero Candida - BEZERRA , Carolina Rabelo Falcão (2020)
Green propolis has been a therapeutic option due to its phytochemical and antifungal diversity acting on different species of Candida, showing satisfactory fungistatic and fungicidal effects, both in vitro and in vivo. A strong relationship between the presence of fixed orthodontic appliances and an increased risk of favoring biofilm stagnation has shown that fungi have virulence factors associated with the development of human disease and increased resistance to antimicrobial agents. This study evaluated the influence of the ethanol extract of green propolis on the adhesion and biofilm of Candida albicans ATCC 443-805-2, Candida tropicalis ATCC 1036-09-2 and Candida parapsilosis ATCC 726-42-6 in dental material. The ethanol extract of green propolis (EEPV) was prepared from 200 g of green propolis diluted in 500 mL of ethyl alcohol PA, stored in an amber flask and kept at room temperature, with stirring for 2 hours / day for 8 days. It was subsequently rotoevaporated and lyophilized and the phytochemical analysis was performed by high performance liquid chromatography. The adhesion of Candida species was performed on stainless steel and acrylic resin fragments and quantified in a Neubauer chamber counting the number of yeast cells adhered to the fragments. Biofilm formation was determined by counting the number of colony forming units (CFU). The intensity of adhesion and biofilm formation was classified as negative, weak, moderate, strong and very strong. Fifteen compounds were identified in the green propolis extract, with 3-hydroxybiochanin A, trimer gallate [epi] catechin and carminic acid as major compounds. The studied species were able to adhere and form biofilm on the surface of stainless steel and acrylic resin and the intensity of adhesion of the yeast cells was weak at all incubation times, except for C. parapsilosis and C. tropicalis, which in 12 h moderate intensity. As for the formation of biofilm (24 and 48 h), it was observed in the metal that C. albicans had moderate intensity in 24 and 48 h; C. parapsilosis at 24 and 48 h had very strong intensity; C. tropicalis in 24 h had a strong intensity and in 48 h very strong. While in resin, all species at times 24 and 48 h had a strong intensity, except for C. tropicalis, which at 48 h had a very strong intensity. The green propolis extract showed antifungal activity and was able to inhibit both adhesion and biofilm formation from 2.5 μg / mL. This study supports the hypothesis that green propolis has antifungal activity and interferes with the virulence factors of C. albicans, C. parapsilosis and C. tropicalis and can be an ally in the prevention of oral infections by the genus Candida in individuals who use prostheses and orthodontic appliances.